EFFECT OF TUBER SOURCE AND VARIETIES ON GROWTH AND YIELD OF FALL SEASON CULTIVATED POTATO IN - Luqman G. Kareem (Mesopotamia Journal of Agriculture)
The experiment was conducted at Kanipanka nursery,Directorate of Agriculture in Sulaimani,Iraq ,during the fall season in order to study the effect of two potato seed sources ; imported and locally produced , two cultivars ; Desiree A and Desiree E in addition to Margarita cultivar on vegetative growth and yield . Factorial experiment using Randomized Complete Block Design (RCBD) with three replicates was applied and the means were compared acoording to L.S.D. at 5%. The results showed the dominance of seeds produced in spring to those imported with regard to : percent of dry matter in vegetative growth , number of aerial stems per plant in ratios of 22.69% and 19.94% successively as well as 40.48%, 40.0 % and 44.92% for tuber wieght , yield per plant and total yield per dounm alternatively . On the other hand, imported potato seeds were dominant significantly to those produced in spring season with respect to height of plants , marketable yield per dounm and protein percent in tubers with ratios 41.59%, 43.78% and 7.23% respctively. As far as cultivars are concerned ; Desiree E was dominant to both Desiree A and Margarita with regard to plant height,number of stemes per plant , weight of tubers , yield per plant ,marketable yield and total yield in ratios : 22.9% , 21.65%, 34. 34%, 34.34%, 4.49%, 22.01%, 13.33% ,46.66%, 1.93%, 45.16% , 19.90% and 51.65% successively .However with regard to the effect of cultivars on some qualitative characteristics, Desiree A was superior to Desiree E and Margarita cultivar with regard to the following : percent of dry matter ,starch and protein in tubers in ratios : 3.0% , 6.74% , 2.39%, 5.37%, 4.12% and 7.65% respectively. Finally the study showed superiority of spring produced potato seeds for most characteristics compared to Desiree E and it is more convenient for fall cultivation in Sulaimani district.